The Significance of the San Remo Manual to Protect the Sea Defense of Indonesia - Rizki Pratama Kamarulah; Lukman Yudho Prakoso (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
In 1994, the San Remo Manual was established as a regulation governing sea warfare, providing guidelines for countries engaged in conflicts at sea. As Indonesia holds a crucial strategic position in both regional and global sea and air zones, understanding and adhering to international law during armed conflicts at sea is of paramount importance. This research aims to offer practical guidance on the significant role of the San Remo Manual, in applying international law during sea warfare and examines its application in Indonesia. The study employs a qualitative method, which seeks to identify and understand various phenomena in-depth. By analyzing different cases and phenomena, empirical insights on the development and application of the law can be derived. The research results show a comprehensive guide for countries involved in sea conflicts, detailing permissible actions, involvement of parties, protection of injured vessels and personnel, and actions taken by non-conflicting nations. For the Indonesian Navy, implementing the San Remo Manual is vital since they operate in waters that may be prone to armed conflicts. Adhering to this manual can help regulate the conduct of naval personnel during military operations at sea, with a strong emphasis on upholding human rights and justice in the use of military force.